Investigation of Ground Water Depletion Pattern across Chennai City - M K, Soundarya; Gurusamy.B, Thanga (International Journal of Engineering and Technology, 2018)
An attempt has been made to investigate both seasonal and long term ground water depletion pattern across the aquifers lying below geographical boundary of Chennai city. The Depth below Ground Level (DBGL) is used as an analyzing parameter for this investigation. This analysis is based on the data that has been made available to the public by Central Ground Water Board (CGWB) and Water Resources Department, Chennai, Tamil Nadu. Both graphical analysis and statistical based regression analysis has been carried out and the result has been presented in graphical and tabular form. Seasonal DBGL variation has been analyzed for the year 2016 after the popular Chennai 2015 December Flood event. It has been observed that the range of ground water level depletion is from 0.1 m per month at Broadway and up to 0.833 m per month at T.S.Campus locations during post monsoon season from January to May. Long term DBGL variation has been analyzed for duration of 22 years from 1996 to 2017. Statistical package for social sciences (SPSS) has been used to perform both linear and other regression analysis. Sustained decrease in ground water level has been observed at locations like Perambur Kodambakkam and Vallalar Nagar during the last two decades.Â